2014
DOI: 10.1039/c4dt01346h
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous citrato-oxovanadate(iv) precursor solutions for VO2: synthesis, spectroscopic investigation and thermal analysis

Abstract: An aqueous precursor solution, containing citrato-VO(2+) complexes, is synthesized for the formation of monoclinic VO2. With regard to the decomposition of the VO(2+) complexes towards vanadium oxide formation, it is important to gain insights into the chemical structure and transformations of the precursor during synthesis and thermal treatment. Hence, the conversion of the cyclic [V4O12](4-) ion to the VO(2+) ion in aqueous solution, using oxalic acid as an acidifier and a reducing agent, is studied by (51)V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The presence of such signal for Au(0)/Au(I) couple clearly suggested that the Au particles in the material was mostly in zero oxidation state and was in accordance with the XRD and DRS study . The other dominant cathodic peak at −1.1 V and its corresponding anodic peak almost at the same potential was due to the [VO 2 ] 2− /[VO 2 ] 3− couple (Figure S2b) . The quasi‐reversible couple appearing at −0.74 V was for VO 2 2+ /VO 2 3+ couple and the peak at 0.69 V was for V (V)/V (IV) couple (Figure S2b) .…”
Section: Resultssupporting
confidence: 86%
“…The presence of such signal for Au(0)/Au(I) couple clearly suggested that the Au particles in the material was mostly in zero oxidation state and was in accordance with the XRD and DRS study . The other dominant cathodic peak at −1.1 V and its corresponding anodic peak almost at the same potential was due to the [VO 2 ] 2− /[VO 2 ] 3− couple (Figure S2b) . The quasi‐reversible couple appearing at −0.74 V was for VO 2 2+ /VO 2 3+ couple and the peak at 0.69 V was for V (V)/V (IV) couple (Figure S2b) .…”
Section: Resultssupporting
confidence: 86%
“…Low angle PXRD pattern of the AgVT catalyst is shown in Figure . PXRD shows the characteristic plane for both silver sulphides and silver vanadates indicating linkage between silver and vanadium through thioglycolic acids . Diffraction peaks observed nearly at 2θ=6.11 is characteristics of those observed in materials with interlayer spacing and the peaks below 2θ=20° may be attributed to the VO 2 + unit …”
Section: Resultsmentioning
confidence: 91%
“…At this stage of the synthesis, the vanadium oxidation state equals +V. The reduction of dioxovanadium(V) to oxovanadium(IV) using oxalic acid occurs in a two-step mechanism, 6,7 starting by the coordination of oxalate anions to dioxovanadium(V), with formation constant K f :…”
Section: ■ Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, the complete reduction of dioxovanadium(V) to oxovanadium(IV) has been shown to be essential for the sol(ution)−gel synthesis of thermochromic vanadium(IV) oxide. 6,7 This exercise can therefore be combined conveniently with the feature article of Parkin and Manning focusing on thin-film deposition of vanadium dioxide and its applications. The method of initial rates is used to determine the rate equation of the redox reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation